1992
DOI: 10.1103/physrevlett.68.2786
|View full text |Cite
|
Sign up to set email alerts
|

Top-site adsorption for potassium on Ni(111)

Abstract: We have used dynamical low-energy electron diffraction (LEED) to determine the adsorption site and the geometry of the surface region for the p(2x2) overlayer of potassium adsorbed on Ni(l I I). The structure consists of the potassium atoms adsorbed on top of the Ni atoms with vertical reconstructions of Ni atoms in the first and second substrate layers combined with a slight horizontal reconstruction of the first substrate layer. The potassium-nickel bond length is found to be 2.82+ 0.04 A corresponding to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Experimentally, in a LEED study at various coverages, this was found to be the only commensurate structure 50 . In a further LEED study 51,52 , the top site was found to be occupied, with a K-Ni distance of 2.82± 0.04Å, a vertical rumpling of the first Ni layer of 0.12Å, and a lateral displacement of 0.06Å of the three nickel atoms in the top layer which are not vertically under the K adsorbate. The adsorption site was later confirmed in SEXAFS measurements 53 , and a larger bond length of 2.92± 0.02Å was obtained.…”
Section: K On the Ni(111) Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally, in a LEED study at various coverages, this was found to be the only commensurate structure 50 . In a further LEED study 51,52 , the top site was found to be occupied, with a K-Ni distance of 2.82± 0.04Å, a vertical rumpling of the first Ni layer of 0.12Å, and a lateral displacement of 0.06Å of the three nickel atoms in the top layer which are not vertically under the K adsorbate. The adsorption site was later confirmed in SEXAFS measurements 53 , and a larger bond length of 2.92± 0.02Å was obtained.…”
Section: K On the Ni(111) Surfacementioning
confidence: 99%
“…Experimentally, using the same technique for both adsorbate systems, it was measured to be slightly shorter and it was speculated that this was due to greater adatomsubstrate interactions involving the partially filled Ni d bands 53 . The possibility of a lateral displacement of the nickel atoms as observed experimentally (0.06Å) 51 was investigated. However, this could not be confirmed and the energy was found to be lowest for the case where this lateral displacement is exactly zero.…”
Section: K On the Ni(111) Surfacementioning
confidence: 99%
“…5,6 For a coverage of about 0.25 ML, K atoms form an ordered p͑2 ϫ 2͒ structure and occupy the atop sites. 7 A photoelectron diffraction ͑PED͒ study of the Ni͑111͒-K / CO system showed there is no change in the adsorption sites for either CO or K upon coadsorption. 8 Recently, the coadsorption of K and CO on Ni͑111͒ was studied with highresolution electron energy loss spectroscopy ͑HREELS͒ by Pacilé et al 9 It was showed that the mechanism underlying the carbon dioxide formation is the Boudouard process ͑CO+CO→ C+CO 2 ͒.…”
Section: Introductionmentioning
confidence: 98%
“…Further confirmation has been provided more recently via high-resolution core level spectroscopy [7] (HRCLS), normal incidence standing x-ray wave field [8] (NISXW), and low energy electron diffraction [9] (LEED). [13] and Ni(100) [14], K and Cs on Ru(0001) [15,16], and Na on Ni(100) [17] [10].…”
mentioning
confidence: 99%